Designing a Network Model for the Russian International Schools - V. A. Yasvin; R. I. Kotov; I. S. Demakov; A. S. Khromykh (Vestnik MGIMO-Universiteta, 2023)
Education is one of Russia's instruments of foreign policy aimed at fostering humanitarian cooperation. Currently, the primary focus is on higher education, while the significance of exporting general education is undervalued. State support measures for existing Russian overseas schools, in accordance with the concepts of "Russian School Abroad" and "Key Directions of Russia's Policy in the Field of International Cultural and Humanitarian Cooperation," are primarily directed toward Russian-speaking compatriots and have little orientation toward broader segments of foreign populations. At the same time, the Concept of the Humanitarian Policy of the Russian Federation Abroad, dated September 5, 2022, explicitly emphasizes the need to expand the network of Russian schools abroad. This article examines a project to establish a network of Russian international schools targeting foreign citizens in a consortium format as a case study that could serve as a model for addressing the stated objective. Particular attention is paid to the socio-political, methodological, and organizationalpedagogical aspects of the project.